(untitled) (Revista Contexto & Saúde, 2026)
This study aims to analyze how Riverside Primary Health Care Unit professionals apply the principles of Lifestyle Medicine in their daily practice. A cross-sectional exploratory study was conducted, using a qualitative approach. The sampled participants were selected from the staff of the Health Unit. They consisted of 16 professionals from the Riverside Family Health Unit, including community health agents, nursing technicians, and higher-level professionals, who participated in four focus groups. Data were collected using a semi-structured interview guide with open-ended questions, applied during focus group meetings. Data analysis was conducted using the IRaMuTeQ software to perform Content Analysis, following the Reinert Method. In the discourse, the speeches and knowledge applied in the work of health professionals were identified, varying according to their role in the Riverside Health Care Center’s health team. The discourse of higher-level professionals focuses on technical issues, while nursing techniques and community health agents focus on user engagement approaches. In the discourse, themes such as sleep, stress, and social connections are strongly related, as well as healthy eating and physical activity. Approaching sensitive topics such as alcohol and toxic Substances seems to be challenging, indicating potential gaps in knowledge or difficulties in structuring effective interventions in this area. Primary care teams need to broaden their understanding of existing management methodologies for self-care education, going beyond professional technical knowledge, and considering the health determinants that interact with individual, familial, and community knowledge.